Histo-Chemical Effects of Iraqi-Camel Colostrum Extracts on Some Liver Biomarkers in Albino Rats - Zainab Ibrahim Mohammed (Journal of Global Pharma Technology, 2020)
This study was intended to investigate the histo-chemical effects of Iraqi camel (Camelus dromedaries) colostrum on liver tissues and enzymes of albino rats, Rattus norvegicus. Colostrum was collected at 30ml at post-parturition times of 0, 6, and 12hr. The colostrum was subjected to an extraction procedure to obtain a filtered fluid that contained bioactive substances. These extracted fluids were given to 4 groups/5 rats each. Group1 (0G), Rats were given 0.1ml of 0hr-colostrum extract orally for 1 week. Group2 (6G), Rats were given 0.1ml of 6hr-colostrum extract orally for 1 week. Group3 (12G), Rats were given 0.1ml of 12hr-colostrum extract orally for 1 week. Group4 (control group, CG), Rats were given tap water only. Body and liver weights were measured every week for 4 weeks. Blood samples and liver samples were collected after 30 days to perform assays of measuring serum proteins and liver enzymes. The results indicate richness of colostrum with protein and fat. The results also revealed increases the levels of liver enzymes and changes in the tissues of the livers. These levels increased especially at 30 days of the experiment for the groups that were given camel colostrum extracts. These results indicate important effects of camel colostrum to prepare and protect body against various environmental intruders such as pathogens. Our results generate important information for future work to thoroughly study colostrum extracts on infections in humans and animals.Keywords: Camel, Colostrum, Liver enzymes, Rats.